Zn Electrodeposition on Single-Crystal GaN(0001) Surface: Nucleation and Growth Mechanism - Fei Peng; Shuang-Jiao Qin; Yu Zhao; Ge-Bo Pan (International Journal of Electrochemistry)
The electrochemical deposition of zinc on single-crystal n-type GaN(0001) from a sulphate solution has been investigated on the basis of electrochemical techniques including cyclic voltammetry, chronoamperometry, and Tafel plot. The morphology and crystal structure of zinc deposits have been characterized by means of scanning electron microscopy, X-ray diffraction, and energy-dispersive X-ray analysis. The result has revealed that the deposition of Zn on GaN electrode commenced at a potential of −1.12 V versus Ag/AgCl. According to the Tafel plot, an exchange current density of ~0.132 mA cm−2 was calculated. In addition, the current transient measurements have shown that Zn deposition process followed the instantaneous nucleation in 10 mM ZnSO4 + 0.5 M Na2SO4 + 0.5 M H3BO3 (pH = 4).